Using captcha technology: pros and cons. ways to secure from spam-bots attacks - Boyko, N.; Stakhiv, M. (Видавництво Львівської політехніки, 2017)
Розглянуто технологію CAPTCHA. Подано алгоритм створення та роботи капчі. Наведено схему роботи капчі. Проаналізовано способи кодування та “ускладнення” зашифрованого тексту. Розглянуто основні способи автоматизованого розпізнавання CAPTCHA. Наведено варіанти визначення тестів CAPTCHA, методи програмних засобів та методи, які не потребують дій від користувача. Проаналізовано переваги та недоліки тестування капчі, а також способи вирішення проблем, що можуть виникати із застосуванням капчі.

This paper is devoted to CAPTCHA technology. Algorithms of creation and work of captcha are described. The scheme of how captcha works is also included. The means of encoding and ‘complication’ of decoded text are described. The main ways of automatic captcha’s recognition are described. Also, it is given in examples options of CAPTCHA’s tests. The programing means that do not require user’s actions are considered. By the way, pros and cons of testing captcha are analyzed. In addition, the main problems that may occur during developing captcha are analyzed.
Keywords: CAPTCHA; алгоритм роботи; інтернет-сервіс; спам-боти; захист; скрипт; кукі; нейронні мережі; CAPTCHA; algorythm of work; Internet service; spam-bots; protection; script; cookies; neural networks; 004.9